Stimulation of c-Myc transcriptional activity by vIRF-3 of Kaposi sarcoma-associated herpesvirus - Lubyová, Barbora; Kellum, Merrill J; Frisancho, Jose A; Pitha-Rowe, Paula (The Journal of biological chemistry, 2007)
Kaposi sarcoma-associated herpesvirus is associated with two lymphoproliferative disorders, primary effusion lymphoma (PEL) and Castleman disease. In PEL, Kaposi sarcoma-associated herpesvirus is present in a latent form expressing only few viral genes. Among them is a viral homologue of cellular interferon regulatory factors, vIRF-3. To study the role of vIRF-3 in PEL lymphomagenesis, we analyzed the interaction of vIRF-3 with cellular proteins. Using yeast two-hybrid screen, we detected the association between vIRF-3 and c-Myc suppressor, MM-1alpha. The vIRF-3 and MM-1alpha interaction was also demonstrated by glutathione S-transferase pulldown assay and coimmunoprecipitation of endogenous vIRF-3 and MM-1alpha in PEL-derived cell lines. Overexpression of vIRF-3 enhanced the c-Myc-dependent transcription of the gene cdk4. Addressing the molecular mechanism of the vIRF-3-mediated stimulation, we demonstrated that the association between MM-1alpha and c-Myc was inhibited by vIRF-3. Furthermore, the recruitment of vIRF-3 to the cdk4 promoter and the elevated levels of the histone H3 acetylation suggest the direct involvement of vIRF-3 in the activation of c-Myc-mediated transcription. These findings indicate that vIRF-3 can effectively stimulate c-Myc function in PEL cells and consequently contribute to de-regulation of B-cell growth and differentiation.
Keywords: Lymphoma, Primary Effusion; Proto-Oncogene Proteins c-myc; techniky dvojhybridového systému; lidé; Interferon Regulatory Factor-3; Gene Library; lidský herpesvirus 8; interferonové regulační faktory; genová knihovna; financování organizované; Viral Proteins; nádorové buněčné linie; Cell Line, Tumor; virové proteiny; Herpesvirus 8, Human; Financing, Organized; Two-Hybrid System Techniques; protoonkogenní proteiny c-myc; Interferon Regulatory Factors; primární efuzivní lymfom; Humans; interferonový regulační faktor 3